The correct expression that uses the Power Rule of Exponents is:
(74)8
Which expression is correctly developed to use the Power Rule of Exponents?(1 point) Responses (74)8 left parenthesis 7 superscript 4 baseline right parenthesis superscript 8 baseline 129 12 superscript 9 baseline (−5)0 left parenthesis negative 5 right parenthesis superscript 0 baseline (78)⋅(710
19 answers
Which of the following correctly used the Power Rule of Exponents in the expression (109)7 ?(1 point) Responses 1063 10 superscript 63 baseline 907 90 superscript 7 baseline 1016 10 superscript 16 baseline 102
The correct expression that uses the Power Rule of Exponents is:
(109)^7
(109)^7
not an answer choice
Apologies for the confusion. The correct answer is:
(10^9)^7 = 10^(9*7) = 10^63
(10^9)^7 = 10^(9*7) = 10^63
If the expression 410 was simplified using the Power Rule of Exponents, what is an equivalent expanded expression? (1 point) Responses (42)8 left parenthesis 4 squared right parenthesis superscript 8 baseline (412)2 left parenthesis 4 superscript 12 baseline right parenthesis squared (45)2 left parenthesis 4 superscript 5 baseline right parenthesis squared 4⋅4⋅4⋅4⋅4⋅4⋅4
The correct equivalent expanded expression for 410, simplified using the Power Rule of Exponents, is:
4^10 = 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4
4^10 = 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4
you sure everything is correct bot?
Apologies for the mistake in my previous response. Let me provide the correct answer.
The equivalent expanded expression for 410, simplified using the Power Rule of Exponents, is:
4^10 = 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 = 1,048,576
The equivalent expanded expression for 410, simplified using the Power Rule of Exponents, is:
4^10 = 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 = 1,048,576
Use the Power Rule of Exponents to create an expression equivalent to (156)2 .(1 point) Responses 1512 15 superscript 12 baseline 154 15 superscript 4 baseline 158 15 superscript 8 baseline 153
The expression equivalent to (156)2, using the Power Rule of Exponents, is:
15^2 = 15 * 15 = 225
15^2 = 15 * 15 = 225
answer choice:
15^12
15^4
15^8
15^3
15^12
15^4
15^8
15^3
The correct answer choice, using the Power Rule of Exponents, is:
15^2
15^2
Use the Power Rule of Exponents to create an expression equivalent to (15^6)^2 .
To find an expression equivalent to (15^6)^2 using the Power Rule of Exponents, we can apply the rule (a^m)^n = a^(m*n).
Therefore, (15^6)^2 simplifies to 15^(6*2), which equals 15^12.
Therefore, (15^6)^2 simplifies to 15^(6*2), which equals 15^12.
What exponent would make the two expressions equivalent: (3^3)^x=32^4
To make the two expressions equivalent, we need to find the value of the exponent x that satisfies the equation (3^3)^x = 32^4.
Using the rule (a^m)^n = a^(m*n), we can rewrite the left side of the equation as 3^(3*x).
32 can be expressed as 2^5.
Therefore, the equation 3^(3*x) = 32^4 can be rewritten as 3^(3*x) = (2^5)^4.
Simplifying further, we have 3^(3*x) = 2^(5*4).
Since the bases on both sides of the equation are the same (3 and 2), we can set the exponents equal to each other:
3*x = 5*4.
Now we can solve for x:
3*x = 20.
Dividing both sides by 3, we get:
x = 20/3.
Therefore, the exponent x that would make the two expressions equivalent is 20/3.
Using the rule (a^m)^n = a^(m*n), we can rewrite the left side of the equation as 3^(3*x).
32 can be expressed as 2^5.
Therefore, the equation 3^(3*x) = 32^4 can be rewritten as 3^(3*x) = (2^5)^4.
Simplifying further, we have 3^(3*x) = 2^(5*4).
Since the bases on both sides of the equation are the same (3 and 2), we can set the exponents equal to each other:
3*x = 5*4.
Now we can solve for x:
3*x = 20.
Dividing both sides by 3, we get:
x = 20/3.
Therefore, the exponent x that would make the two expressions equivalent is 20/3.
What exponent would make the two expressions equivalent: (3^3)^x=3^24
To find the exponent that would make the two expressions equivalent, we can set the exponents equal to each other in the equation (3^3)^x = 3^24.
Using the rule (a^m)^n = a^(m*n), we can rewrite the left side of the equation as 3^(3*x).
Thus, we have 3^(3*x) = 3^24.
Since the bases on both sides of the equation are the same (3), we can set the exponents equal to each other:
3*x = 24.
Solving for x:
x = 24/3 = 8.
Therefore, the exponent x that would make the two expressions equivalent is 8.
Using the rule (a^m)^n = a^(m*n), we can rewrite the left side of the equation as 3^(3*x).
Thus, we have 3^(3*x) = 3^24.
Since the bases on both sides of the equation are the same (3), we can set the exponents equal to each other:
3*x = 24.
Solving for x:
x = 24/3 = 8.
Therefore, the exponent x that would make the two expressions equivalent is 8.